Anti-Diabetic Effects of an Ethanol Extract of Cassia Abbreviata Stem Bark on Diabetic Rats and Possible Mechanism of Its Action - Anti-diabetic Properties of Cassia abbreviata - - Keagile Bati; Tebogo Elvis Kwape; Padmaja Chaturvedi (Korean Pharmacopuncture Institute, 2017)
Objectives: This study aimed to evaluate the hypoglycemic effects of an ethanol extract of Cassia abbreviata (ECA) bark and the possible mechanisms of its action in diabetic albino rats. Methods: ECA was prepared by soaking the powdered plant material in 70% ethanol. It was filtered and made solvent-free by evaporation on a rotary evaporator. Type 2 diabetes was induced in albino rats by injecting 35 mg/kg body weight (bw) of streptozotocin after having fed the rats a high-fat diet for 2 weeks. Diabetic rats were divided into ECA-150, ECA-300 and Metformin (MET)-180 groups, where the numbers are the doses in mg.kg.bw administered to the groups. Normal (NC) and diabetic (DC) controls were given distilled water. The animals had their fasting blood glucose levels and body weights determined every 7 days for 21 days. Oral glucose tolerance tests (OGTTs) were carried out in all animals at the beginning and the end of the experiment. Liver and kidney samples were harvested for glucose 6 phosphatase (G6Pase) and hexokinase activity analyses. Small intestines and diaphragms from normal rats were used for α-glucosidase and glucose uptake studies against the extract. Results: Two doses, 150 and 300 mg/kg bw, significantly reduced the fasting blood glucose levels in diabetic rats and helped them maintain normal body weights. The glucose level in DC rats significantly increased while their body weights decreased. The 150 mg/kg bw dose significantly increased hexokinase and decreased G6Pase activities in the liver and the kidneys. ECA inhibited α-glucosidase activity and promoted glucose uptake in the rats' hemi-diaphragms. Conclusion: This study revealed that ECA normalized blood glucose levels and body weights in type 2 diabetic rats. The normalization of the glucose levels may possibly be due to inhibition of α-glucosidase, decreased G6Pase activity, increased hexokinase activity and improved glucose uptake by muscle tissues.